The energy, environmental and economic impacts of carbon tax rate and taxation industry: A CGE based study in China - Lin, Boqiang; Jia, Zhijie (Energy (Oxford), 2018)
Human activities have led to increase in carbon dioxide emissions, and carbon tax is one of the main policy tools for reducing global emissions. This paper constructs nine scenarios considering different carbon tax rates and the different taxable industries to analyze the impact of Carbon Tax System (CTS) on energy, environment and the economy. We find that the negative impact of CTS on GDP is acceptable, and the maximum scenario will not exceed 0.5%. If carbon taxes are levied on energy-intensive enterprises, the impact on carbon emissions is also relatively small, even if the carbon tax rate is relatively high. Higher carbon tax rate will result in higher CO2 emission reduction and higher marginal CO2 emission reduction of CTS. The carbon tax rate follows the "law of increasing marginal emission reduction". We also argue that the focus of taxation should be on energy enterprises. It is only in this way that the efficiency of the energy market can be fully implemented to conserve energy and reduce emissions. This paper suggests that China should adopt CTS that simultaneously imposes a higher tax on energy companies and energy-intensive enterprises. This will maximize emissions reductions and have only a small impact on GDP. •The negative impact of CTS on GDP is acceptable, and the maximum scenario will not exceed 0.5%.•The focus of carbon taxation should be on energy enterprises.•The carbon tax rate follows the "law of increasing marginal emission reduction".•China should adopt carbon tax policy that simultaneously imposes a high tax rate on energy companies and energy-intensive enterprises.